ENVIRONMENTAL ANALYSIS AS A BASIS FOR DETERMINING STRATEGY OF COOPERATIVE UNITS IN AMBON CITY - Rumra Suryanti Ismail (Journal of Economics, Business, and Accountancy Ventura, 2012)
Cooperation is either a grass-root economic movement or an entity having role in achievingprosperity society. Cooperation need to build itself and should be built to be self-reliantbased on its principles so that it will become national economic foundation. Therefore, cooperationis hoped to be a stable, democratic, autonomous, participative and social economicorganization. This research aimed at analyzing ability of internal factors (organization andinstitution, effort and business, service, member participation) or external factor (network) ofKUD in measuring performance level as well as determining strategy alternatives whichwere appropriate with performance level of KUD. This research used Cooperative CapacityAnalysis (CCA) with scoring technique and Basic Main Strategy Selection Matrix in choosingappropriate strategy for the KUD. Research showed that internal and external factor wereable to determine the level of performance of KUD and grouped in two groups namely Goodand Moderate. KUD classified as good was suggested to choose intensive strategy alternativeby focusing on Concentrated Growth, Product Development and Market Development.While KUD classified as moderate was suggested to choose defensive strategy alternative byfocusing on Goal Changing strategy.